Revision of the Subgenus Coprochara Mulsant & Rey of the Genus Aleochara Gravenhorst from Japan (Coleoptera: Staphylinidae: Aleocharinae) - Yamamoto, Shûhei; Maruyama, Munetoshi (Zootaxa, 2013)
A taxonomic revision of the subgenus Coprochara Mulsant & Rey, 1874 of the genus Aleochara Gravenhorst, 1802 in Japan is presented. The following three species are recognized: Aleochara (C.) verna Say, 1833, A. (C.) binotata Kraatz, 1856 and A. (C.) squalithorax Sharp, 1888, of which A. binotata is new to Japan. All previous records of “A. (C.) bipus-tulata (Linnaeus, 1760)” should be regarded as misidentifications of either A. verna or A. binotata. New records are added for, A. squalithorax, a littoral species. All species are redescribed, figured, keyed and mapped.